Pembuatan Pupuk Kompos dengan Pemanfaatan Cow Dung (Kotoran Lembu) Desa Kuala Indah Kecamatan Sei Suka Kabupaten Batu Bara - Zulia Hanum; Anggie Safitri (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Kuala Indah Village, Sei Suka Subdistrict, Batu Bara Regency is one of the abundant oil palm producing villages with a variety of rich marine resources. Based on the results of observations made in Kuala Indah Village, there is a lot of green land that is used by villagers to make cattle farms as a supporting activity in earning income. In addition, there is a lot of beach waste in the form of garbage from the waves of the sea that can be used in making compost using cow dung (cow dung) by livestock groups in Kuala Indah Village. On the other hand, the COVID-19 pandemic has caused the community's economy to decline and the main activity of the Livestock Group in Kuala Indah Village, the Putra Tanjung Bersama Livestock Group, has become quiet. With these problems, the author initiated a training in making compost using cow dung (cow dung). The method of implementing the training is done by training in theory and direct practice of making compost using a mixture of dolomite. This training directly involved the head of the Tanjung Bersama Putra Cattle Cattle Group. The purpose of the training is to provide insight into how to make compost from the use of cow dung (cow dung) which can be made and used personally, and can be marketed to increase economic needs. With the composting program from KKN Mandiri activities, it can increase the empowerment of the Kuala Indah Village community and can effectively minimize the impact of livestock waste, and can be used as an alternative to the use of environmentally friendly compost.